2012
DOI: 10.1515/jpem-2011-0467
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of sex development among Sudanese children: 5-year experience of a pediatric endocrinology clinic

Abstract: DSDs are not uncommon in Sudan. Because of lack of awareness and sociocultural reasons cases are referred late. Investigating these cases is expensive and has to be supported, and more multidisciplinary teams have to be trained to make services accessible and affordable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 0 publications
2
22
3
1
Order By: Relevance
“…Similar finding of erroneous incidence has been reported in other anomalies in our setting as well as in some other developing countries [9][10][11]14]. Perhaps, some cases of DSD do not come to the attention of the main stream medical Pediatr Surg Int practitioners and the reported cases were based only on those that presented at the tertiary care centres.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar finding of erroneous incidence has been reported in other anomalies in our setting as well as in some other developing countries [9][10][11]14]. Perhaps, some cases of DSD do not come to the attention of the main stream medical Pediatr Surg Int practitioners and the reported cases were based only on those that presented at the tertiary care centres.…”
Section: Discussionsupporting
confidence: 88%
“…Reports from sub-Saharan Africa indicate that socio-cultural factors, resource deficiency, and lack of facilities add to the challenges of DSD management [9][10][11]. The net effect is that outcome of DSD in this setting is less satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of 46,XX DSD was CAH 21-hydroxylase deficiency (52 of 62 cases with a proven aetiology), whereas androgen insensitivity was the most frequent cause of DSD in 46,XY individuals. 70% of all 122 cases were born to first-cousin marriages [84] . A further small study of 26 DSD cases from Sudan observed parental consanguinity in 70% of cases, 10% reported no consanguinity, whilst 20% did not provide sufficient family history to ascertain consanguinity [85] .…”
Section: Discussionmentioning
confidence: 99%
“…Some DSDs present with genital appearance that does not permit prompt gender declaration, and this physical appearance is called ambiguous genitalia, the criteria of which are well discussed elsewhere. In this retrospective study, we have diagnosed 40 cases over a 6-year period, which is the second publication from Sudan (Abdullah et al 2012). This indicates that this is an important clinical problem in Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…The initial stabilization of infants with DSD requires attention to both medical and psychosocial issues. In Sudan, 70 % of deliveries occur at home and midwives and young doctors are not trained on this issue, and therefore, the gravity of the situation is not well appreciated (Abdullah et al 2012). Even when referred early, some families refuse to go to doctors because it is considered a stigma or because of financial reasons they cannot travel to these centers.…”
Section: Discussionmentioning
confidence: 99%